Sociodemographic Predictors of Knowledge and Attitude of Married Males About Antenatal and Post-Natal Needs of Women in the General Population of Rawalpindi; A Cross-Sectional Study - Adnan, Anoosha; Malik, Maryam Noor; Ali, Muhammad Sairis; Nedia Zaineb; Hooria Fatima; Frooq, Bushra (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Socioeconomic, cultural, religious, and ethnic disparities hinder women's health decisions. Male involvement in antenatal and post-natal health programs can improve outcomes. Objective: The objective is to assess the level of knowledge and attitudes among married males regarding the antenatal and postnatal needs of women in Rawalpindi. Material and methods: A cross-sectional study involving 323 married males for 06 months, was conducted using a self-structured validated questionnaire. Data was analyzed using IBM SPSS version 26.0. Results: 49.2% of male participants had adequate knowledge, 26.9% had poor knowledge, and 23.5% had excellent knowledge. Attitude assessment showed that 35.6% had poor attitudes, 37.5% had adequate attitudes, and 26.9% had excellent attitudes. Significant association of knowledge was found with education, residence, monthly income and number of children. Conclusion: Good education, better income, and number of children positively influenced knowledge of antenatal and postnatal care, but similar trends were not observed for attitudes. Increased awareness and community education are needed. Keywords: Antenatal care, Postnatal care, Maternal health